ANALISIS KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA SMA PADA MATERI TURUNAN FUNGSI ALJABAR - Nurita Dwi Rahmawati; Lessa Roesdiana (Department of Mathematics Education, Universitas Kuningan, 2022)
Concept understanding is a skill to explore concepts related to mathematics. There are some students who still find it difficult to understand mathematical concepts due to internal and external factors. This study aims to describe the ability to understand mathematical concepts of high school students on the material of Algebraic Function Derivatives. The approach in this study is a qualitative approach using descriptive methods. The research subjects that will be used are 32 students of class XII MIPA. The sample selection used was purposive sampling with random sampling of 3 students for high ability, 3 students for medium ability, and 3 students for low ability. Data collection techniques by providing a mathematical concept understanding test. The data analysis technique used is the Miles and Huberman technique. The indicators on the ability to understand mathematical concepts are 1) linking various concepts, 2) restate the concept, and 3) the ability to classify objects according to certain characteristics according to the concept. In this study, the percentage of students' ability to understand mathematical concepts, including the first and second indicators, was 87.5% and the third indicator was 3.125%. This can guarantee that the first and second indicators show that students can relate linking various concepts and restate the concept of application for the indicators, indicating that there are still many students who are not able the ability to classify objects according to certain characteristics according to the concept.